Regenerated cellulose/montmorillonite and graphene nanocomposites via ionic liquids [electronic resource] - Shaya Mahmoudian, 1979- (2012)
Thesis (Doktor Falsafah (Kejuruteraan Polimer)) - Universiti Teknologi Malaysia, 2012